HYDROCARBON HABITAT IN RIFT GRABEN SUB-BASIN JAMBI - SUDARMAWAN , DRIANTO
Sub-Basin of Jambi, particularly in the area Jabung has proven to be a sub-basin oil producers. Oil production resulting from the western region of which Indonesia is the contribution of this sub-basin. Examples of oil from 14 wells taken from the six oil fields that represent the center and east of the area Jabung and from various reservoir, are analyzed to determine characteristics of the oil produced from this Jabung area. Oil correlation of oil in the area showed an average Jabung is a type of light oil until very lightly with API gravity values ranging between 32º and 46.1º, only the oil samples from the North Betara the value of its API gravity indicates that the value of 28.0º included in the classification of the oil medium. All the oil samples have relatively similar composition and plotted in oil region and has the maturity level of less mature till most mature. The correlation of oil to the oil resources of oil produced shows generally come from rock deposited in terrestrial, fluvio-deltaic environments, except oil in North Field Betara-04 which comes from rock that was deposited in lacustrine environments. Source rocks are generally deposited on the rift system in Betara Deep and Geragai Deep filled by fluvial-deltaic sediments. Indications lacustrine sediments at depths of only the northern part Betara possible only a small part of the Rift system.